(untitled) (Teaching and Learning Inquiry, 2019)
This paper describes a course called The First Year Experience: Mapping our Communities designed around a theme of asset mapping, which allowed us to organically integrate a number of pedagogical goals with a number of high-impact practices. The mapping metaphor extended from physical mapping of the university campus as a space to the mapping of academic and social resources, including mapping of the students’ sense of self and goals, their new environment and all the assets available to help them succeed. The theme of asset mapping also encompassed different world views and the concepts of perspective and positionality to provide students with a critical perspective on their own understanding and its limits. Our research assesses the success of this course at meeting its many intertwined goals, based on both quantitative and qualitative data collected from students in two recent course offerings.